Pentingnya Produk Hijau dan Gaya Hidup Terhadap Niat Membeli Makanan Organic di Masa Pandemi Covid 19 - Widi Dewi Ruspitasari (UNIVERSITAS PGRI MADIUN, 2021)
The Covid 19 pandemic hit the whole world, especially in Indonesia. This pandemic period requires people to take better care of their health, one of which is by consuming healthy foods that are beneficial to the body. There are several restaurants in Malang that offer healthy food in the form of salads and smoothies. The purpose of this study was to determine the effect of green products and lifestyle on the intention to buy healthy food in the city of Malang. The number of samples in this study were 75 consumers. Quantitative data collected through questionnaires were analyzed using PLS analysis. The results showed that both green products and lifestyle had a great influence on purchase intentions. The strongest factor in green products is the composition of the content, so green products must pay attention to the ingredients in their salads and smoothies. Because the better the vegetables and fruits used, the faster the benefits will be felt by consumers. While the strongest factor that exists in the lifestyle is family interest, where when the family gets used to eating organic food, this will become a habit, which will be carried out continuously and will make it a lifestyle.